Assessment of promising sugarcane clones for yield and juice quality attributes at final selection stage (Zoo Botanica, 2025)
Sugarcane is a major cash crop of Pakistan, grown for sugar, jaggery, and by-products such as ethanol, molasses, and bagasse, and it plays a significant role in the national economy of Pakistan. In order to evaluate the agronomic and sugar recovery percentage of promising sugarcane clones for their selection at final stage and commercial cultivation; ten sugarcane genotypes/clones were evaluated for agronomic performance and sugar recovery percentage over various harvesting dates during crushing seasons. Significant dissimilarity was noted among genotypes for tillers per plant, germination percentage, millable cane population, sugarcane yield and juice quality characters. Data depicted that the germination percentage and sugarcane yield was ranged from 20.9 to 55.5% and 62.3 and 108.7 t ha⁻¹ respectively across all genotypes. Average sugar recovery percentage over sampling dates ranged from 12.05 (S2015-SL-444) to 12.68 percent (S2013-US-917). Based on pooled assessment the two genotypes specifically S2015-SL-89 and S2015-SL-289 were retained due to a satisfactory balance of cane yield and juice quality, while the other cane genotypes were rejected due to one or more limiting factors such as low sucrose content, poor crop stand, lodging, low cane yield, red rot susceptibility and cane brittleness. The findings indicate the importance of integrating both crop quantitative yield components and juice quality parameters in final selection stages of breeding programs for commercial sugarcane cultivation.
Keywords: Sugarcane genotypes; sugar recovery; millable canes; clone selection